CCR3 Expression and Function in Asthmatic Airway Smooth Muscle Cells - Joubert, Philippe; Lajoie-Kadoch, Stephane; Labonte, Isabelle; Gounni, Abdelilah Soussi; Maghni, Karim; Wellemans, Vincent; Chakir, Jamila; Laviolette, Michel; Hamid, Qutayba; Lamkhioued, Bouchaib (The Journal of immunology (1950), 2005)
Asthma is characterized by an increase in airway smooth muscle mass and a decreased distance between the smooth muscle layer and the epithelium. Furthermore, there is evidence to indicate that airway smooth muscle cells (ASMC) express a wide variety of receptors involved in the immune response. The aims of this study were to examine the expression of CCR3 on ASMC, to compare this expression between asthmatic and nonasthmatic subjects, and to determine the implications of CCR3 expression in the migration of ASMC. We first demonstrated that ASMC constitutively express CCR3 at both mRNA and protein levels. Interestingly, TNF-α increases ASMC surface expression of CCR3 from 33 to 74%. Furthermore, using FACS analysis, we found that ASMC CCR3 is expressed to a greater degree in asthmatic vs control subjects (95 vs 75%). Functionality of the receptor was demonstrated by calcium assay; the addition of CCR3 ligand eotaxin to ASMC resulted in an increase in intracellular calcium production. Interestingly, ASMC was seen to demonstrate a positive chemotactic response to eotaxin. Indeed, ASMC significantly migrated toward 100 ng/ml eotaxin (2.2-fold increase, compared with control). In conclusion, the expression of CCR3 by ASMC is increased in asthmatics, and our data show that a CCR3 ligand such as eotaxin induces migration of ASMC in vitro. These results may suggest that eotaxin could be involved in the increased smooth muscle mass observed in asthmatics through the activation of CCR3.